Digital hemispherical photography for estimating forest canopy properties: current controversies and opportunities - Chianucci F; Cutini A (iForest - Biogeosciences and Forestry, 2012)
Hemispherical photography has been used since the 1960s in forest ecology. Nevertheless, specific constraints related to film cameras have progressively prevented widespread adoption of this photographic method. Advances in digital photographic technology hold great promise to overcome the major drawbacks of hemispherical photography, particularly regarding field techniques and image processing aspects. This contribution is aimed to: (i) provide a basic foreground of digital hemispherical photography; (ii) illustrate the major strengths and weakness of the method; (iii) provide an reliable protocol for image acquisition and analysis, to get the most out of using hemispherical photography for canopy properties extraction.